2023
DOI: 10.3390/agriculture13050973
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Organic Additives for Replanted Soil in Apple Tree Production in a Fruit Tree Nursery

Abstract: How soil is used affects its production characteristics in the future. Under ARD (Apple Replant Disease) conditions, replanted soil’s physical, chemical and biological properties deteriorate. Their improvement is possible through, for example, increasing the content of organic matter in the soil. The study aimed to assess the effect of two organic additives for replanted soil on its physical, chemical and biological properties, as well as on the vegetative growth of apple trees of the ‘Gala Schniga SchniCo(s)’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Zhao et al (2023) showed that soil phosphatase activity increased significantly and then decreased with the increase in the number of years of planting tomato in the facility. Zydlik et al (2023) showed that adding biochar to apple orchards could increase soil protease activity and improve the soil environment. Ren et al…”
Section: Rhizosphere Soil Enzymes Of Pear Trees Of Different Planting...mentioning
confidence: 99%
“…Zhao et al (2023) showed that soil phosphatase activity increased significantly and then decreased with the increase in the number of years of planting tomato in the facility. Zydlik et al (2023) showed that adding biochar to apple orchards could increase soil protease activity and improve the soil environment. Ren et al…”
Section: Rhizosphere Soil Enzymes Of Pear Trees Of Different Planting...mentioning
confidence: 99%